Martinez de la Rosa's "Edipo": some considerations about the Opus Perfectum of Greek drama in 19th century Spain - Gallé Cejudo, Rafael (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
Martínez de la Rosa had a solid humanistic background and a confessed inclination for the Greek and Latin classics. So the classical heritage can be traced in almost every field of his extensive literary production. One of the most significant examples is, without a doubt, the tragedy Edipo—premiered in 1832—. This work occupies a unique position in the Spanish Neoclassicism for a important part of the critics.
Keywords: Francisco Martínez de la Rosa; Oedipus Rex; Sophocles